Upaya Konservasi Ikan Bilih (Mystacoleucus padangensis) dengan Penetapan Ukuran Tangkap dan Suaka di Danau Singkarak - Andri Warsa; Didik Wahju Hendro Tjajo; Lismining Pujiyani Astuti (Jurnal Airaha, 2020)
Bilih (Mystacoleucus padangensis) is endemic fish with high economic value in Lake Singkarak. Overexploitation with unselective fishing gears caused population decreasing. Its effect for fishermen income decreasing so they need an effort for fish conservation with the determination of length at first captured and fish sanctuary. The objective of the research is the determination of length at first captured and fish sanctuary as an effort for bilih conservation at Lake Singkarak. The research was done at July and September 2019 in two location namely Aripan and Sumpur. Bilih sample was got by experimental fishing using gillnet with mesh size 5/8; ¾ and 1,0 inci; cast net, and Alahan. Result of the research shown the size for bilih exploitation is ≥ 9.0 cm and used the gillnet with 1.0 inch mesh size. The fish sanctuary at Sumpur River can give some bilih seed as 1.29 million and fish with legal-size and mature condition 182 thousand. Determination of legal size and fish sanctuary give impact for exploitation sustainability and increasing fishermen income at Lake Singkarak.